Performance of Biophysical Mangrove Ecosystems in Birem Bayeun and Rantau Selamat Sub-District, East Aceh KERAGAAN BIOFISIK EKOSISTEM MANGROVE DI KECAMATAN BIREM BAYEUN DAN KECAMATAN RANTAU SELAMAT, ACEH TIMUR - Nurlailita .; Cecep Kusmana; Widiatmaka . (Jurnal Silvikultur Tropika, 2015)
Mangrove ecosystem has role of interface ecosystem between land and sea. Some anthropogenic factors are responsible for the damage of mangrove ecosystem. The purposes of this research are to explore the performance of the biophysical mangrove ecosystems at Birem Bayeun and Rantau Selamat Sub-District, East Aceh. Some analyses done in this study are: the analysis of vegetation, environment properties, and analysis of area and distribution of mangrove. The results show that mangroves in the study area consist of 10 species, in which R. apiculata and B. gymorrhiza have dominant species in the study area, Importance Value Index (IVI) that is higher than the other species. Based on the interpretation of citra image, width of mangroves in the study area has been reduced. Biophysical properties of the mangrove area were suitable for mangrove growth (Physical-chemical properties of the soil, the chemical properties of water (salinity), inundation class and the frequency of tidal).Key words : anthropogenic, biophysical, ecosystem, mangrove.